The Effectiveness and Safety of Tibial-Sided Osteotomy for Fibula Untethering in Lateral Close-Wedge High Tibial Osteotomy: A Novel Technique with Video Illustration - Keun Young Choi; Man Soo Kim; Yong In (Medicina)
Background and Objectives: Despite its advantages, lateral close-wedge high tibial osteotomy (LCWHTO) requires proximal tibiofibular joint detachment (PTFJD) or fibular shaft osteotomy for gap closing. These fibula untethering procedures are technically demanding and not free from the risk of neurovascular injuries. Our novel fibula untethering technique, tibial-sided osteotomy (TSO) near the proximal tibiofibular joint (PTFJ), aims to reduce technical demands and the risk of injury to the peroneal nerve and popliteal neurovascular structures. The purposes of this study were to introduce the TSO technique and compare the complexity and safety of TSO with those of radiographic virtual PTFJD, which is defined based on radiographic landmarks representing the traditional PTFJD technique. Materials and Methods: Between March and December 2023, 13 patients who underwent LCWHTO with TSO for fibula untethering were enrolled. All patients underwent MRI preoperatively and CT scanning postoperatively. The location of the TSO site on the postoperative CT scans was matched to preoperative MRI to measure the shortest distance to the peroneal nerve and popliteal artery. These values were compared with estimates of the distance between the PTFJ and neurovascular structures in the radiographic virtual PTFJD group. The protective effect of the popliteus muscle was evaluated by extending the osteotomy direction toward the posterior compartment of the knee. Results: The TSO procedure was straightforward and reproducible without producing incomplete gap closure during LCWHTO. On axial images, the distances between the surgical plane and the peroneal nerve or popliteal artery were significantly longer in the TSO group than in the radiographic virtual PTFJD group (both p = 0.001). On coronal and axial MRI, the popliteus muscle covered the posterior osteotomy plane in all patients undergoing TSO but did not cover the PTFJD plane in the radiographic virtual PTFJD group. Conclusions: Our novel TSO technique for fibula untethering during LCWHTO is reproducible and reduces the risk of neurovascular injury by placing the separation site more medially than in the PTFJD procedure.